HYGIENIC PRINCIPLES OF WEIGHT CONTROL IN MILITARY SERVANTS THROUGH HEALTHY DIET AND PHYSICAL ACTIVITY - Jamshid A. Kutliev; Shukrullo A. Yaxyaev; Bakhtior A. Axmedov (Web of Journals Publishing, 2024)
This study presents the results of scientific research conducted to evaluate the effectiveness of weight management strategies through comprehensive measures for healthy nutrition and adequate physical activity under military service conditions.